Production Management in SME's Industry: Case Study of CV Wiracana - Apriani Kurnia Suci; Desman Hidayat; Andhi Bharata (Binus Business Review, 2015)
Production Management is the act of designing, operating, and improving the productive systems – a system for getting the work done. Along the process, the synergy in between machineries, facilities and people could empower the sustainable of the production. In fact, for some cases, the implementation of unique system is needed for the production process. The example for this transformation production management is in the case of CV Wiracana, a handmade manufacturing company for folding hand fans from Bali. CV Wiracana's products are very unique, combined from mass production for the speed and an art for the custom made product. At one side, the market forces them to speed up the production and for this purpose, they must set up the new system on their production line. On the other side, the masterpiece also needs to be produced without jeopardizing mass production line schedule. The transformation production system needs to be done no later than 2015 as the urgency to fulfill the customer demand, business growth, compete in the industry and sustainability. The changes are expected to improve the production at least about 20% or doubled from the current production.